Terbium Medical Radioisotope Production: Laser Resonance Ionization Scheme Development - Gadelshin, Vadim Maratovich; Formento Cavaier, Roberto; Haddad, Ferid; Heinke, Reinhard; Stora, Thierry; Studer, Dominik; Weber, Felix; Wendt, Klaus (Frontiers in Medicine, 2021)
Terbium (Tb) is a promising element for the theranostic approach in nuclear medicine. The new CERN-MEDICIS facility aims for production of its medical radioisotopes to support related R&D projects in biomedicine. The use of laser resonance ionization is essential to provide radioisotopic yields of highest quantity and quality, specifically regarding purity. This paper presents the results of preparation and characterization of a suitable two-step laser resonance ionization process for Tb. By resonance excitation via an auto-ionizing level, the high ionization efficiency of 53% was achieved. To simulate realistic production conditions for Tb radioisotopes, the influence of a surplus of Gd atoms, which is a typical target material for Tb generation, was considered, showing the necessity of radiochemical purification procedures before mass separation. Nevertheless, a tenfold enhancement of the Tb ion beam using laser resonance ionization was observed even with Gd:Tb atomic ratio of 100:1.